Pengaruh Literasi Keuangan dan Literasi Digital terhadap Preferensi Bank Digital di Kalangan Mahasiswa - Ananda Meylani Puteri; Intan Inanda; Rifaldy Bagas Prasetio (Jurnal Publikasi Ilmu Manajemen, 2024)
In the era of the Industrial Revolution 4.0, digital technology has become an important factor in the banking industry, including the increasing use of digital services such as mobile banking and e-wallets. This study aims to analyze the influence of financial literacy and digital literacy on students' preferences in using digital banks. Given the rapid growth of digital banks in Indonesia, it is important to understand the factors that influence students' preferences, especially financial literacy and digital literacy skills. This study uses a quantitative approach with a survey method involving students from several universities in Indonesia. The data were analyzed using regression analysis to see the influence of financial literacy and digital literacy variables on digital bank preferences. The results of the study show that both financial literacy and digital literacy have a significant influence on students' preferences in choosing digital banks, with digital literacy having a greater influence. These findings provide important implications for financial institutions in designing appropriate marketing strategies for the student segment.